Pengendalian Kimia dan Resistensi Vektor Anopheles Dewasa pada Kawasan Endemis Malaria di Dunia - Musfirah, Musfirah (Universitas Ahmad Dahlan, 2017)
Background: Various methods of malaria vector control has been done. Insecticides which using repeatedly impact new problems for the emergence of vector resistance. Hence, optimization about active ingredient in the insecticide product should take notice to the development of insecticide resistance mechanisms for malaria vectors. Literature review which assess and discuss adult Anopheles sp resistance for chemical control programme were still limited to certain insecticides. The aim of this literature review is collecting and findings evidence has been produced by researchers which associated with chemical control of vector and variety of adult Anopheles resistance as a strategy to eradicate malaria endemic cases. Method: This literature review prepared by systematic review methods.Google database is used as the primary source of search with keyword